DÖPPELGANGER - Polydorou, Doros (My University, 2026)
A Digital + VR Exhibition: https://www.yevkravt.com/doppelgranger DÖPPELGANGER is a digital and VR exhibition, curated by Yev Kravt. My role in this work was to design the digital exhibition, taking into consideration the concept and the work of the invited artists. Concept: We live in a time of endless reflection. One body, many selves, physical and digital, authentic and fabricated, curated and corrupted, fractured across timelines, networks and platforms. The notion of the doppelgänger has haunted human consciousness for centuries, surfacing in ancient myth, in psychoanalysis, in cinema, and now in the very devices we keep in our pockets. Today, it is not merely a spectral figure or literary trope; it is a login, a bot, a dataset. A silent algorithmic mirror that watches, predicts and sometimes betrays. The Doppelgänger exhibition, curated by Yev Kravt, brings together 13 digital artists, designers and architects whose practices engage with mirroring and multiplicity. Some approach these themes philosophically, others through a social lens. Some address it performatively, with an air of deliberate deceit. All of those featured here work on the same unsettling question: In a world where everything can be copied, what remains that is still real? Seeing Double Throughout history and across cultures, the double has served as both aspiration and threat, representing our hopes as well as our fears. In myth, the twin can take the form of a divine companion, a ghostly spirit, a paranormal appearance or an embodiment of the soul. Though our interest in the double might be ancient, our new reality multiplies the self by design, across social media, virtual worlds and AI-driven platforms. This exhibition unfolds entirely within a digital copy of the TAITEEN TALO in Finland, a 3D-rendered replica of the physical space in Turku. Visitors enter through a specially designed virtual pavilion; once nside, an underground corridor reveals artworks that appear familiar, variations on known paintings, sculptures or architectural forms, yet they have all been warped by algorithmic processes and machine learning. AI in many ways is a replica of human behaviour: it trains itself on our images, our words, our ideas and our histories. At its core, it is the ultimate doppelganger of all that has ever existed. What happens when your reflection no longer reflects you? Can a double outlive the self? And in a world where everything can be copied, what remains real? As we scroll through social feeds, enter dialogue with AI assistants or slip into VR headsets, do we become more connected or more fragmented? Are we glimpsing our future or confronting new shadows? The doppelgänger speaks to the tension between these extremes, between liberating multiplicity and existential dread, between transcendent self-knowledge and inescapable self-deception.The artists, designers and architect in Doppelgänger. Reflections, Replicas, and the Self in the Age of the Digital Double approach many of the aforementioned questions from every angle; some embrace the beauty of fluid identities, while others reveal the potential dangers of manipulation and echo chambers. The TAITEEN TALO in Finland becomes a stage where illusions meet realities, leaving visitors to navigate a labyrinth of layered narratives. Through this carefully-choreographed journey, you might just find that the most unsettling reflection is the one that greets you in the mirror each morning. Featured Artists Adonis Archontides (Cyprus), Alex Valentina (Italy), Benjamin Pompe (the Netherlands), Eva Papamargariti (Greece), Fabiana de Barros (Brasil / Swiss), Faysal Mroueh (Cyprus), Gohar Martirosyan (Armenia), Jonas Lund (Sweden), Kevin Bray (France), Maria Touloupou (Cyprus), Michalis Charalambous (Cyprus), Mike Pelletier (Canada) and PET LIGER (Cyprus). Team Curator: Yev Kravt Digital Exhibition: Designer Doros Polydorou Graphic Design: Angeriki | Poster Image: Mike Pelletier Text Editor: George King Production Taiteen Talo: Ville Laaksonen